Faktor-Faktor Yang Berhubungan Dengan Kelelahan Kerja Tenaga Kerja Bongkar Muat (TKBM) Pelabuhan Tanjung Emas Semarang - Bellinda Annisa Putri; Anik Setyo Wahyuningsih (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the International Labour Organization (ILO), two million workers die each year due to work accidents due to fatigue. Work accidents experienced have a significant relationship with work fatigue. Finally, it results in decreased work capacity and individual physical endurance. The purpose of this study is specifically to determine the factors related to work fatigue with TKBM. In general, it is to determine the relationship between age, nutritional status, education level, insight, medical history, length of service and manual material handling on work fatigue of TKBM Tanjung Emas Port, Semarang. The type of research applied is quantitative using a correlation approach. The design applied is cross-sectional. After analyzing the data and conducting statistical tests using the Chi Square test, the results obtained were age (p-value = 0.002); nutritional status (p-value = 0.143); education level (p-value = 0.135); insight (p-value = 0.018); medical history (p-value = 0.041); length of service (p-value = 0.031); manual material handling (p-value = 0.007). The conclusion that can be drawn from this study is that there is a relationship between age, insight, medical history, length of service and manual material handling with work fatigue, and there is no relationship between nutritional status and level of education with work fatigue.